2013
DOI: 10.5243/jsswr.2013.4
|View full text |Cite
|
Sign up to set email alerts
|

Transitioning from Homelessness: A “Fresh-Start” Event

Abstract: Permanent supportive housing (PSH) has been recognized as central to the goal of ending chronic homelessness. This qualitative study considers the positive and negative expectations of 31 men and women in the Skid Row area of Los Angeles who are beginning the transition from homelessness to PSH through a Housing First approach. This study uses in-depth, qualitative interviews and an inductive approach informed by sensitizing concepts derived from the literature and thematic analysis of case summaries, intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 32 publications
5
38
1
3
Order By: Relevance
“…This study further confirms that housing is an important foundation from which to build and act on hope, providing participants with hopes for experiences of control, independence and security and an opportunity to sleep, reflect and care for their physical and mental health. These findings support the notion of increased ontological security, reflecting an increased sense of security, safety and predictability that can be enhanced by permanent housing, which has been noted in research on Housing First interventions with homeless individuals with serious mental illness 27 31. These findings expand on this research by connecting the importance of increased ontological security to hope-building and recovery processes in that the receipt of actual, but also anticipated housing, can stimulate a sense of ontological security which can further build and support action on hope, a key component in the recovery process 12 13 27…”
Section: Discussionsupporting
confidence: 79%
“…This study further confirms that housing is an important foundation from which to build and act on hope, providing participants with hopes for experiences of control, independence and security and an opportunity to sleep, reflect and care for their physical and mental health. These findings support the notion of increased ontological security, reflecting an increased sense of security, safety and predictability that can be enhanced by permanent housing, which has been noted in research on Housing First interventions with homeless individuals with serious mental illness 27 31. These findings expand on this research by connecting the importance of increased ontological security to hope-building and recovery processes in that the receipt of actual, but also anticipated housing, can stimulate a sense of ontological security which can further build and support action on hope, a key component in the recovery process 12 13 27…”
Section: Discussionsupporting
confidence: 79%
“…The sense of security and positive self-worth resulting from good-quality, stable housing allowed individuals to explore new daily routines, reduce substance use and antisocial behaviour, expand social roles and networks, and provided a safe space to reflect on one's experiences. The breadth of domains affected by stable housing supports the construct of ontological security—the psychosocial sense of safety and stability which often accompanies permanent housing 31 34. Past research has shown that homeless adults with mental illness who receive HF manifest greater ontological security than those living in transitional housing 31.…”
Section: Discussionmentioning
confidence: 94%
“…The structural and individual factors that contributed to homelessness (ie, poverty and lack of resources, poor mental and physical health, poor coping skills, lack of meaningful activities) continued to impact all participants’ daily lives. Henwood et al 34 suggest that past trauma may lead individuals to view the world as dangerous and unpredictable, thus leading some people to seek the perceived comfort of isolating in an apartment. This isolation could be a necessary consolidation phase before more substantial recovery can occur 21.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the personal confidence and hope (M=3.84, SD=0.670) also had high scores. Hope, seen as a maintaining factor and trigger in the process of recovery has been identified in the literature as a crucial component in an youth's ability to recover (Kirst et al, 2014;Padgett, Henwood, Abrams, & Drake, 2008;Padgett & Henwood, 2011, 2012Henwood et al, 2013;. Personal confidence has been associated with one's ability to define purpose and meaning in their life (Jacobson & Greenley, 2001;Mancini, 2008;Resnick et al, 2005;.…”
Section: Theory Of Interpersonalmentioning
confidence: 99%